Greene, Ricardo (ed.) (2014). Ciudad Fritanga - Trimano, Luciana Geraldine (Documents d'Anàlisi Geogràfica, 2017)
Greene, Ricardo (ed.) (2014) Ciudad Fritanga Santiago de Chile: Bifurcaciones, 205 p. ISBN 9569501006